Dark Participation in Games - Kowert, Rachel (Frontiers in Psychology, 2020)
With the advent of digital games came the advent of gamer cultures and identities. A “gamer” became a new social first for the group of individuals who played video games (primarily in arcades) in the late 1970’s. Over time, however, gamer cultures have grown into what is largely discussed as “toxic cultures,” and come to become more associated with exclusion than inclusion if you don’t fit a certain mold. Despite its prevalence, deviant behaviors in games as a subject of academic study is a confusing space, with different researchers using different criteria to describe the same things. This article provides the first comprehensive cataloging and overview of dark participation in games. This includes defining these behaviors, cataloging their variants, discussing their social and psychological impact and their potential underpinnings. It is critical to establish a shared language about what these behaviors are in order to effectively understand and combat them.